Perilaku konsumen dalam memilih simpanan dan pembiayaan di KSPPS Berkah Abadi Gemilang Jepara - Edi Susilo; Alfin Iqbal Rifqi Ardiansyah (Proceeding of Conference on Islamic Management, Accounting, and Economics, 2019)
This study aims to determine the effect of Consumer Behavior, Products, Promotion and Service on Savings and Financing Products. This research is a quantitative research. The population in this study is the community and members of KSPPS Berkah Abadi Gemilang. The sample in this study was calculated by Slovin formula, there were 100 respondents. The research sampling technique was insindental sampling, data analysis used multiple regression using Statistical Product and Service Solution (SPSS) Software version 24. The results of this study showed partially that the variables of Consumer Behavior, Product, Promotion and Service Behavior had a significant positive effect on savings products and financing. Simultaneously, variables of Consumer Behavior, Products, Promotions and Services variables have a significant effect on savings and financing products.